دور الترجمة الروائية في التواصل مع الآخر رواية "الحزام" لأحمد أبو دهمان أنموذجاً - زوقار بلقاسم; لواج أحلام; ملاحي علي (Maalim, 2026)
This research paper aims to show the role of fiction translation in cross-fertilization cultures on the basis that it is one the most important linguistic communicative means to get to know the other, or allow the latter know the…ego, this is through our reading of foreign texts into our language or translating Arabic texts into other languages. This is why the Saudi novelist Ahmed Abu Dahman sought to translate his novel, Al-Hazam. So what are the mechanisms used by Ahmed Abu Dahman in translating his narrative text? And can the translated text necessarily be considered the original text? And did this translation contribute to introducing Saudi literature? And to what extent can translation be considered a factor in cross-fertilization of cultures? Key words: general translation, literary translation, translation techniques, cross-fertilization.